ANALISIS PENGARUH HARGA, PENDAPATAN, LOKASI, DAN FASILITAS TERHADAP PERMINTAAN RUMAH SUBSIDI: (Studi Kasus Perumahan Planet Green TAMBORA Lamongan) - Luluk Nur Azizah (STIE Mahardhika, 2019)
The nature of housing or residence does not only cover the house from the physical side of the building, but also covers all the supporting facilities both inside and outside. This study aims to analyze and find empirical evidence of the effect of prices, income, location, and facilities on the demand for housing houses of subsidies TAMBORA Lamongan The population used in this study was the Head of the Family (KK) who occupied a house of subsidies in Planet Green Housing TAMBORA Lamongan as many as 485 households. While the sample used in this research is 100 respondents The method used more precisely is to use Simple Random Sample. Using Multiple Regression Analysis Based on the results of the analysis, it shows that prices, revenues, location, and facilities influence the demand for houses on Planet Green TAMBORA. From the testing of the coefficient of determination, it is known that 77.2% of the variation that occurs in the home demand variable by customers is influenced by variables of price, income, location, and facilities. While the remaining 22.8% is influenced by other factors. Based on the results of this study, it was found that the facility factor had a significant influence on the demand for houses on Planet Green TAMBORA. It can be seen from the level of coefficients that affect the demand for housing facilities at 0.249; location of 0.231; income of 0.195; and the price is equal to 0.149.